Effects of TPH2 gene variation and childhood trauma on the clinical and circuit-level phenotype of functional movement disorders. Issue 8 (23rd June 2020) - Spagnolo, Primavera A; Norato, Gina; Maurer, Carine W; Goldman, David; Hodgkinson, Colin; Horovitz, Silvina; Hallett, Mark
Abstract : Background: Functional movement disorders (FMDs), part of the wide spectrum of functional neurological disorders (conversion disorders), are common and often associated with a poor prognosis. Nevertheless, little is known about their neurobiological underpinnings, particularly with regard to the contribution of genetic factors. Because FMD and stress-related disorders share a common core of biobehavioural manifestations, we investigated whether variants in stress-related genes also contributed, directly and interactively with childhood trauma, to the clinical and circuit-level phenotypes of FMD. Methods: Sixty-nine patients with a 'clinically defined' diagnosis of FMD were genotyped for 18 single-nucleotide polymorphisms (SNPs) from 14 candidate genes. FMD clinical characteristics, psychiatric comorbidity and symptomatology, and childhood trauma exposure were assessed. Resting-state functional connectivity data were obtained in a subgroup of 38 patients with FMD and 38 age-matched and sex-matched healthy controls. Amygdala–frontal connectivity was analysed using a whole-brain seed-based approach. Results: Among the SNPs analysed, a tryptophan hydroxylase 2 ( TPH2 ) gene polymorphism—G703T—significantly predicted clinical and neurocircuitry manifestations of FMD. Relative to GG homozygotes, T carriers were characterised by earlier FMD age of onset and decreased connectivity between the right amygdala and the middle frontal gyrus. Furthermore, the TPH2 genotype showed a significant interaction with childhood trauma in predicting worse symptom severity. Conclusions: This is, to our knowledge, the first study showing that the TPH2 genotype may modulate FMD both directly and interactively with childhood trauma. Because both this polymorphism and early-life stress alter serotonin levels, our findings support a potential molecular mechanism modulating FMD phenotype.